Evaluation of p-wave Dispersion and Left Atrium Ejection Fraction in Patients with Cardioembolic Ischemic Stroke (Research, Society and Development, 2021)
Introduction: Studies show that p-wave dispersion and left atrial ejection fraction are predictors of cardiovascular events. Purpose: To verify the association of p-wave dispersion and left atrial ejection fraction with cardioembolic ischemic stroke. Methods: This is an observational, cross-sectional, case-control study with 61 patients, mean age of 65.6, with sinus rhythm ischemic stroke who underwent clinical evaluation with CHA2DS2-VASc score, electrocardiogram, echocardiogram and ultrasonography with Doppler of both carotid and vertebral arteries. The groups were divided into cardioembolic (cases) and non-cardioembolic (controls). The p-wave dispersion was obtained with a 12-lead electrocardiographic tracing at 50 mm/s by subtracting the largest p-wave by the smallest one. Left atrial ejection fraction was obtained using the modified biplane Simpson method. This study was approved by the UERN Research Ethics Committee (# 2,536,483). Results: Mean values for p-wave dispersion were 62.5 ms for cases and 49 ms for controls (p = 0.025). For left atrial ejection fraction, the cases presented a mean of 42.9% and the controls a mean of 55.8% (p = 0.003). For the CHA2DS2-VASc score, the mean values were 3.6 and 3.1 for cases and controls, respectively (p = 0.35). Cardiovascular risk factors showed similar distribution in both groups. Conclusion: p-wave dispersion and left atrial ejection fraction were associated with the cardioembolic patients with sinus rhythm that have gone through ischemic stroke.